Comparative study of the relationship between manual and scanning methods for spinal braces / Ahmed Mohammed Nasser Albadwi - Ahmed Mohammed, Nasser Albadwi (2018)
Scoliosis is a structural 3- dimensional deformity of the spine that occurs more often during the growth of an individual just before reaching the age of puberty. Variant options are available to treat this spine deformity. The three major options could either be observation, surgery or orthotics(bracing) depending on the angle of the curvature a proper treatment may take place. Cobb angle is a term used for the measuring of the curvature severity. Orthotics are mostly used when the Cobb angle 20-45°. However, there are also variant types of orthotics(bracing) and fabrication techniques may as well differ. This research aims to conduct a comparison between two methods of fabricating the orthotic devices (Spinal braces). Manual(conventional) versus scanning technique (BioSculptor). Using each method, three subjects were recruited and we were able to fabricate two spinal braces for each of the three subjects. Few variations in circumference measurements were observed, and the average percentage difference between the two braces fabricated was 5.9% in circumference parameter. However, it was found that the manual method was more flexible than the scanning in a few aspects compared with CAD/CAM system, even though the scanning method proved to be more efficient and less messy. This result made us concludes that there are many factors effecting the fabrication process depending on the experience in making orthoses either manually or by using scanning technique.